Mechanistic investigation of mEos4b reveals a strategy to reduce track interruptions in sptPALM - De Zitter, Elke; Thédié, Daniel; Mönkemöller, Viola; Hugelier, Siewert; Beaudouin, Joël; Adam, Virgile; Byrdin, Martin; Van Meervelt, Luc; Dedecker, Peter; Bourgeois, Dominique (Nature methods, 2019)
Green-to-red photoconvertible fluorescent proteins repeatedly enter dark states, causing interrupted tracks in single-particle-tracking localization microscopy (sptPALM). We identified a long-lived dark state in photoconverted mEos4b that results from isomerization of the chromophore and efficiently absorbs cyan light. Addition of weak 488-nm light swiftly reverts this dark state to the fluorescent state. This strategy largely eliminates slow blinking and enables the recording of longer tracks in sptPALM with minimum effort.